(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The present text unfolds, deepens and discusses the process notes that the duo of authors has written together over the course of a decade of working on curricular components concerning dance dramaturgies in formal dance education contexts in the city of Fortaleza/CE. The curricular component "Dance Dramaturgies" is part of the four educational contexts that will be discussed here: Dance graduates (Bachelor and Licentiate) and Dance Technicians from the Escola Porto Iracema das Artes and the Centro Cultural do Bom Jardim. In this article, the teaching work is narrated from an ethical-political approach with regard to the aesthetics of dance. Since dramaturgical work requires careful reading and listening to the context, this article also includes a presentation of the recent history of contemporary dance in Ceará, only those points that can elucidate, even briefly, its context.